Constrained algorithms for multi input adaptive lattices in array processing - Durrani, T.; Murukutla, N.; Sharman, K. (ICASSP '81. IEEE International Conference on Acoustics, Speech, and Signal Processing, 1981)
This paper is concerned with problems of enhancing the look-direction signal in the presence of spatially distributed interference sources and sensor noise, when a multi channel processor is employed subject to the constraint that it has a desired frequency response for look-direction signals. The multi-channel algorithms to be presented possess stage by stage decoupling and do not involve an arbitrary size of the step length, unlike conventional tapped delay line algorithms. General implementation of constraints are discussed in terms of multi channel adaptive lattice algorithms. Different structures are proposed for the constraint algorithms based, on a direct form and a normalised form, which may be applied to broad-band sensor data. Single channel multi-sensor adaptive lattices are considered for narrow-band array data processing and their performance compared with eigenfilter (Pisarenko) type processors.